1998
DOI: 10.1074/jbc.273.32.20535
|View full text |Cite
|
Sign up to set email alerts
|

Tuberous Sclerosis Gene 2 Product Modulates Transcription Mediated by Steroid Hormone Receptor Family Members

Abstract: Tuberous sclerosis (TSC) is a genetic disorder that results in the development of hamartomatous lesions in a variety of organ systems. Both the prevalence of the disease and the often devastating consequences of these tumors pose a serious health and medical care problem. The disease has been mapped to two distinct genetic loci in humans, and although the genes (TSC1 and TSC2) for both loci have recently been cloned, their function remains an enigma. Data presented here demonstrates that TSC2 protein can bind … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
80
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(82 citation statements)
references
References 49 publications
2
80
0
Order By: Relevance
“…Tuberin contains a domain that interacts with steroid receptor families, especially with glucocorticoid receptor, to form a complex. 32 This complex is a negative regulator of the transcriptional activity of glucocorticoid receptor. Expression of glucocorticoid receptor in uterus is basically unknown until a recent study from rat uterus showed moderate expression of glucocorticoid receptor in normal endometrium and smooth muscle of the myometrium.…”
Section: Discussionmentioning
confidence: 99%
“…Tuberin contains a domain that interacts with steroid receptor families, especially with glucocorticoid receptor, to form a complex. 32 This complex is a negative regulator of the transcriptional activity of glucocorticoid receptor. Expression of glucocorticoid receptor in uterus is basically unknown until a recent study from rat uterus showed moderate expression of glucocorticoid receptor in normal endometrium and smooth muscle of the myometrium.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that it binds to the TSC2 gene product, probably through coiled-coil domains and that it localizes to as yet uncharacterized structures within the cytoplasm (van Slegtenhorst et al, 1998). The TSC2 gene product has been reported to have a GTPase activating protein (GAP) domain and transcription activation domains and has been shown to be a modulator of RXR mediated transcription (Henry et al, 1998) suggesting a role in the regulation of cellular di erentiation. Two other observations that have previously been made suggest possible areas where the TSC1 gene product may function.…”
mentioning
confidence: 99%
“…Tuberin and hamartin are multifunctional proteins associated with cell adhesion (31), cell cycle/ proliferation (27,28), and transcriptional signaling (30). Hamartin and tuberin may function in different cellular locations.…”
Section: Discussionmentioning
confidence: 99%
“…This complex is a strong negative regulator of the transcriptional activity of GCR (30). GCR is known to be an important factor influencing gastric mucosal function and morphology (32,48).…”
Section: Discussionmentioning
confidence: 99%